The Christianization of the Peruvian indigenous - Marzal, Manuel (1969)
I present in these pages the most important points of the Christianization of the Peruvian indigenous. I limit myself to the evangelizing task during the 16th century and only on some points -such as the fight against idolatry- do I extend well into the 17th century. By Christianization I understand the reception of baptism and a series of values, rites and norms that can be considered Christian.